NF-KappaB in Long-Term Memory and Structural Plasticity in the Adult Mammalian Brain - Kaltschmidt, Barbara; Kaltschmidt, Christian (Frontiers in Molecular Neuroscience, 2015)
The transcription factor nuclear factor kappaB (NF-κB) is a well-known regulator of inflammation, stress, and immune responses as well as cell survival. In the nervous system, NF-κB is one of the crucial components in the molecular switch that converts short- to long-term memory—a process that requires de novo gene expression. Here, the researches published on NF-κB and downstream target genes in mammals will be reviewed, which are necessary for structural plasticity and long-term memory, both under normal and pathological conditions in the brain. Genetic evidence has revealed that NF-κB regulates neuroprotection, neuronal transmission, and long-term memory. In addition, after genetic ablation of all NF-κB subunits, a severe defect in hippocampal adult neurogenesis was observed during aging. Proliferation of neural precursors is increased; however, axon outgrowth, synaptogenesis, and tissue homeostasis of the dentate gyrus are hampered. In this process, the NF-κB target gene PKAcat and other downstream target genes such as Igf2 are critically involved. Therefore, NF-κB activity seems to be crucial in regulating structural plasticity and replenishment of granule cells within the hippocampus throughout the life. In addition to the function of NF-κB in neurons, we will discuss on a neuroinflammatory role of the transcription factor in glia. Finally, a model for NF-κB homeostasis on the molecular level is presented, in order to explain seemingly the contradictory, the friend or foe, role of NF-κB in the nervous system.